The Effect of Self-Compassion and Islamic Spiritual Orientation on Academic Anxiety - Ningrum, Fuja Septia; Purwanto, Edy; Mulawarman, Mulawarman (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2021)
High anxiety level which can disrupt students’ concentration and reduce their memory performance results in less focus, confusion, and less optimal learning in terms of comprehending subject materials. Thus, this study attempted to analyze the effects of self-compassion and Islamic spiritual orientation on academic anxiety. It involved students from four public schools in Semarang as population. Further, they were sampled using cluster random sampling technique and resulted 350 students. After some analyses were carried out, it was known that there was a negative and significant effect of self-compassion and Islamic spiritual orientation on students’ academic anxiety, while self-compassion and Islamic spiritual orientation on academic anxiety reduction can be understood through changes in positive self-perception.